2020
DOI: 10.1021/acs.analchem.9b04526
|View full text |Cite
|
Sign up to set email alerts
|

Free Flow Ion Concentration Polarization Focusing (FF-ICPF)

Abstract: Electrokinetic separation techniques in microfluidics are a powerful analytical chemistry tool, although an inherent limitation of microfluidics is their low sample throughput. In this article we report a free-flow variant of an electrokinetic focusing method, namely ion concentration polarization focusing (ICPF). The analytes flow continuously through the system via pressure driven flow while they separate and concentrate perpendicularly to the flow by ICPF. We demonstrate free flow ion concentration polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…13 Many existing ICP-based preconcentrators operate at > 100 V, which hinders integration into portable devices. Further, improvement of volumetric throughput, 2,14,15 integration with downstream analysis, [16][17][18][19] and the development of strategies to decrease fluidic instability are active areas of research. 20,21 Fluidic instability (evidenced by size and magnitudes of vortex flow near the electrode), which is caused by steep gradients in electrolyte concentration and electric field strength and exacerbated by increased device dimensions, leads to unwanted mixing, ultimately limiting sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many existing ICP-based preconcentrators operate at > 100 V, which hinders integration into portable devices. Further, improvement of volumetric throughput, 2,14,15 integration with downstream analysis, [16][17][18][19] and the development of strategies to decrease fluidic instability are active areas of research. 20,21 Fluidic instability (evidenced by size and magnitudes of vortex flow near the electrode), which is caused by steep gradients in electrolyte concentration and electric field strength and exacerbated by increased device dimensions, leads to unwanted mixing, ultimately limiting sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the device in [ 33 ], the microfluidic device we study is composed of a chamber surrounded by four microchannels arrays. Surfaces of the microchannels at the upper and lower sides of the chamber are positively charged.…”
Section: Methodsmentioning
confidence: 99%
“…In recent work, Papadimitridou et al reported a new system to focus (and separate) charged particles [ 33 ]. In their system, sample solutions were pumped horizontally from left to right (as in Figures of [ 33 ]) through a macroscale chamber, with all the chamber walls formed by large arrays of microchannels. In the meantime, an electric field was applied in the perpendicular direction (vertically from top to bottom as in Figures of [ 33 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of analytes electrokinetically focused via ion concentration polarization focusing (ICPF) has been reported before by our group 1,2 and a number of other researchers. [3][4][5][6][7][8] Continuous extraction methods such as our previous work and the work 2 of Kwak et al 5 suffer from low preconcentration rates. On the other hand in non-continuous methods, after extraction a significant decrease in concentration and separation resolution inevitably occurs due to diffusion.…”
Section: Introductionmentioning
confidence: 92%